2017
DOI: 10.1002/pola.28551
|View full text |Cite
|
Sign up to set email alerts
|

The use of polymers in Li‐S batteries: A review

Abstract: Recent developments in the use of polymeric materials as device components in lithium sulfur (Li-S) batteries are reviewed. Li-S batteries have generated tremendous interest as a next generation battery exhibiting charge capacities and energy densities that greatly exceed Li-ion battery technologies. In this Highlight, the first comprehensive review focusing on the use of polymeric materials throughout these devices is provided. The key role polymers play in Li-S technology is presented and organized in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 272 publications
(279 reference statements)
0
94
0
1
Order By: Relevance
“…See Figure S1 for the reaction scheme. Yield: 9.80 g (80%); mp 5 228-231 8; 1 NMR (400 MHz, DMSO-d 6 The solution of (CF 3 SO 2 ) 2 NLi (6.64 g, 23.1 mmol) in 15 mL of distilled water was added dropwise to the solution of 3,3bis(4-aminophenyl)-(N-ethyl)quinuclidinium iodide (8.00 g, 17.8 mmol) in 60 mL of H 2 O:EtOH (3:1 by volume) mixture under stirring at ambient temperature. The stirring was continued for 2 h and the precipitation of the bright yellow solid was observed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…See Figure S1 for the reaction scheme. Yield: 9.80 g (80%); mp 5 228-231 8; 1 NMR (400 MHz, DMSO-d 6 The solution of (CF 3 SO 2 ) 2 NLi (6.64 g, 23.1 mmol) in 15 mL of distilled water was added dropwise to the solution of 3,3bis(4-aminophenyl)-(N-ethyl)quinuclidinium iodide (8.00 g, 17.8 mmol) in 60 mL of H 2 O:EtOH (3:1 by volume) mixture under stirring at ambient temperature. The stirring was continued for 2 h and the precipitation of the bright yellow solid was observed.…”
Section: Methodsmentioning
confidence: 99%
“…The powder was collected by filtration, thoroughly washed with water and dried at 80 8/1 mm Hg for 12 h. See Figure S1 for the reaction scheme. Yield: 9.87 g (92%); mp 5 182-183 j ; 1 NMR (400 MHz, DMSO-d 6…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a stronger interaction between the polymer and the different sulfur composites takes place, because of the presence of specific functional groups in the polymeric structure. 12,40 Although polymers were originally thought as more likely materials to be incorporated into cathodes, with respect to metal oxides, a tendency to the study and exploration of the latter has been recently observed. Later on, the synthesis of hybrid composite materials, where both polymer and metal oxides are used, has been reported.…”
Section: A6120mentioning
confidence: 99%
“…11,12 To the best of our knowledge, this important field has not yet been reviewed or critically analyzed as a whole, except for two reviews on polymeric compounds only 12,40 and a recent review on nanostructured metal oxides and sulfides. 41 In the present review, we wish to present and discuss the performance of those non-carbonaceous materials, making a special emphasis on publications in the field from the last eight years.…”
Section: A6120mentioning
confidence: 99%